Functionally engineered egg albumen gel for quasi-solid dye sensitized solar cells - Kelkar, Sarika A.; Pandey, Komal; Agarkar, Shruti A.; Saikhedkar, Nidhi; Tathavadekar, Mukta; Agrawal, Ishita; Gundloori, Rathna V. N.; Ogale, Satishchandra (ACS Sustainable Chemistry & Engineering, 2014)
In this report, we demonstrated an interesting application of a bioderived material for the dye sensitized solar cells (DSSCs). Egg white, the clear liquid in a hen's egg, which possesses a remarkable gelling/cross-linking ability, was applied in the form of a gel electrolyte in a DSSC architecture to enhance its durability. A hybrid gel composed of poly(acrylic acid), polyaniline and egg albumen was synthesized, and the cell efficiency, stability and durability of the corresponding DSSC device were studied in detail. The dye sensitized solar cell with the egg albumen based electrolyte demonstrated a conversion energy efficiency of 4.6%. Further, a chemically modified egg albumen with ethylenediaminetetraacetic dianhydride showed improved cross-linking, microstructural and conductivity properties of the gel, and yielded a remarkable 5.75% conversion efficiency. Electrochemical impedance spectroscopy data showed favorable characteristics for charge transport through the modified gel and supported the efficiency observations very well.
Keywords: dye sensitized solar cells; Egg albumen; gel electrolyte

Cathepsins of lepidopteran insects: aspects and prospects - Saikhedkar, Nidhi; Summanwar, Aarohi; Joshi, Rakesh S.; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2015)
Molecular understanding of lepidopteran physiology has revealed that proteases consist of one of the central regulatory/reacting system for insect growth and survival. Among the various proteases, cathepsins are the most crucial cellular proteases, which play vital roles during insect development. In the present review, we have discussed various aspects of the lepidopteran insect cathepsins, emphasizing their roles in processes like development, growth, metamorphosis, apoptosis and immunity. Cathepsins are categorized into different types on the basis of their sequence diversification, leading to variation in structure and catalytic function. Cathepsins exhibit tissue and stage specific expression pattern which is fine-tuned by a delicate balance of expression, compartmentalization, zymogen activation, inhibition by protein inhibitors and degradation. The indispensability of cathepsins as cellular proteases in the above mentioned processes proposes them as novel targets for designing effective and specific insect controlling strategies. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Apoptosis; Cathepsin; Cysteine/aspartate protease; Development; Lepidoptera; Pest control; Stress response